2021
DOI: 10.1002/hbm.25390
|View full text |Cite
|
Sign up to set email alerts
|

Selective morphological and volumetric alterations in the hippocampus of children exposed in utero to gestational diabetes mellitus

Abstract: Prior epidemiological studies have found that in utero exposure to gestational diabetes mellitus (GDM) is associated with increased risk for neurodevelopmental disorders. However, brain alterations associated with GDM are not known. The hippocampus is pivotal for cognition and emotional regulation. Therefore, we assessed relationships between in utero exposure to GDM and hippocampal morphology and subfield structure during childhood. One hundred seventeen children aged 7-11 years (57% girls, 57% exposed to GDM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 42 publications
0
21
2
Order By: Relevance
“…There were marginally significant findings that children prenatally exposed to maternal diabetes had smaller total surface area and total subcortical gray matter volume. Compared with previous studies [10][11][12] , ABCD study consisted of a larger and more diverse pediatric population across 21 sites in the US. The directionality of group differences were consistent with prior imaging studies [10][11][12] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There were marginally significant findings that children prenatally exposed to maternal diabetes had smaller total surface area and total subcortical gray matter volume. Compared with previous studies [10][11][12] , ABCD study consisted of a larger and more diverse pediatric population across 21 sites in the US. The directionality of group differences were consistent with prior imaging studies [10][11][12] .…”
Section: Discussionmentioning
confidence: 99%
“…Compared with previous studies [10][11][12] , ABCD study consisted of a larger and more diverse pediatric population across 21 sites in the US. The directionality of group differences were consistent with prior imaging studies [10][11][12] . Effect sizes observed in brain outcomes were small yet comparable with other disorders observed in youth, such as attention deficit hyperactivity disorder, ASD, obsessive compulsive disorder, and major depressive disorder [35][36][37] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Abnormal maternal glucose metabolism during pregnancy leads to alterations in the intrauterine environment that can interfere with fetal brain development. Existing researches have found that the shape and volume of the hippocampus in IDM may be affected by intrauterine hyperglycemia ( 27 ). The hippocampus is a subcortical structure critical for learning, memory and emotion regulation ( 28 ), and hippocampus impairment may affect neurological function either directly or by breaking off neural connections.…”
Section: Discussionmentioning
confidence: 99%